The influence of extrachromosomal elements in the anthrax “cross-over” strain Bacillus cereus G9241 - Taylor-Joyce, Grace; Manoharan, Shathviga; Brooker, Thomas A.; Hernández-Rodríguez, Carmen Sara; Baillie, Les; Oyston, Petra C. F.; Hapeshi, Alexia; Waterfield, Nicholas R. (Frontiers in Microbiology, 2023)
Bacillus cereus G9241 was isolated from a welder who survived a pulmonary anthrax-like disease. Strain G9241 carries two virulence plasmids, pBCX01 and pBC210, as well as an extrachromosomal prophage, pBFH_1. pBCX01 has 99.6% sequence identity to pXO1 carried by Bacillus anthracis and encodes the tripartite anthrax toxin genes and atxA, a mammalian virulence transcriptional regulator. This work looks at how the presence of pBCX01 and temperature may affect the lifestyle of B. cereus G9241 using a transcriptomic analysis and by studying spore formation, an important part of the B. anthracis lifecycle. Here we report that pBCX01 has a stronger effect on gene transcription at the mammalian infection relevant temperature of 37°C in comparison to 25°C. At 37°C, the presence of pBCX01 appears to have a negative effect on genes involved in cell metabolism, including biosynthesis of amino acids, whilst positively affecting the transcription of many transmembrane proteins. The study of spore formation showed B. cereus G9241 sporulated rapidly in comparison to the B. cereus sensu stricto type strain ATCC 14579, particularly at 37°C. The carriage of pBCX01 did not affect this phenotype suggesting that other genetic elements were driving rapid sporulation. An unexpected finding of this study was that pBFH_1 is highly expressed at 37°C in comparison to 25°C and pBFH_1 expression leads to the production of Siphoviridae-like phage particles in the supernatant of B. cereus G9241. This study provides an insight on how the extrachromosomal genetic elements in B. cereus G9241 has an influence in bacterial phenotypes.